"Rent a mom" and other services: markets, meanings and emotions. (13th September 2005) - Hochschild, Arlie Russell
In this essay, the author explores the impact of commercialisation on emotional life. She considers three approaches to the topic – theories of modernisation, of cultural variation and of capitalist encroachment. Drawing elements from each, she outlines what amounts to a preface to a sociology of emotions approach to commercialisation.